(untitled) (Journal of Partial Differential Equations, 2024)
In this paper, we consider a coupled Lamé system with a viscoelastic damping in the first equation and two strong discrete time delays. We prove its existence by using the Faedo-Galerkin method and establish an exponential decay result by introducing a suitable Lyapunov functional.